Isolation of Endophytic Fungi from Algerian Plant Salicornia arabica and Screening of their Antimicrobial Activity - Nouari Sadrati; Amina Zerroug; Benselhoub Nedjemeddine; Hamadi Sofiane (Turkish Journal of Agriculture: Food Science and Technology)
The present study was aimed at isolating endophytic fungi from the Algerian medicinal plant Salicornia arabica and analyzing its antifungal and antibacterial effects. The morphological analysis allowed us to identify endophyte isolates at the genus level as belonging to 8 different genera, Aureobasidium sp., Ulocladium sp., Acremonium sp., Stemphylium sp., Penicillium sp., Aspergillus sp., Phoma sp., and Chrysosporium sp. with frequency percentages 6.7%, 13.3%, 20%, 13.3%, 13.3%, 13.3%, 6.7%, 6.7%, respectively. The antimicrobial activity was caried out using the agar plug diffusion method. The three isolates of the genus Acremonium sp. were highly active against all tested bacteria except Enterococcus faecalis. Comparison of the means of inhibition zones of the active isolates showed that the three fungal isolates of Acremonium were the most active, followed by Chrysosporium sp., Penicillium sp.1, Aureobasidium sp., Stemphylium sp.1, Penicillium sp. .2, and Ulocladium sp.2. The widest zones of inhibition were 22.33 and 20.33mm for Acremonium sp.3, 18.33 and 15.33mm for Aureobasidium sp., 19.33mm for Penicillium sp.1, and 19 and 15mm for Stemphylium sp.1 obtained against Bacillus cereus and Staphylococcus aureus bacteria, respectively. Regarding the antifungal activity, the best inhibitory activity was 80 and 64.70% obtained with the isolate Penicillium sp.2 against Fusarium oxysporum f.sp. ciccri and Fusarium oxysporum f.sp. albedinis, respectively, and of 63.29 and 58% observed against Phytophthora infestans and Fusarium oxysporum f.sp. ciccri, respectively, with the endophytic isolate Aspergillus sp.2. These results indicated the possible prospect of endophytes fungi isolated from Salicornia arabica as a promising resource of antimicrobial compounds and in the quest for the potential starting points for the development of new antibiotics.